Основы экотехносферной безопасности: учебное пособие - Букейханов Н. Р. Нурым Раимжанович; Чмырь И. М. Инна Михайловна; Гвоздкова С. И. Светлана Ильинична; Бутримова Е. В. Елена Владимировна; Никишечкин А. П. Анатолий Петрович; Кулизаде Д. И. Дмитрий Игорьевич (Москва, Инфра-Инженерия, 2021)
Авт. указаны на обороте тит. л.